2022
DOI: 10.1158/1940-6207.capr-22-0113
|View full text |Cite
|
Sign up to set email alerts
|

Reversing the Genomic, Epigenetic, and Triple-Negative Breast Cancer–Enhancing Effects of Obesity

Abstract: The reversibility of the procancer effects of obesity was interrogated in formerly obese C57BL/6 mice that lost weight via a nonrestricted low-fat diet (LFD) or 3 distinct calorie-restricted (CR) regimens (low-fat CR, Mediterranean-style CR, or intermittent CR). These mice, along with continuously obese mice and lean control mice, were orthotopically injected with E0771 cells, a mouse model of triple-negative breast cancer. Tumor weight, systemic cytokines, and incidence of lung metastases were elevated in the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(35 citation statements)
references
References 48 publications
1
34
0
Order By: Relevance
“…Preclinical studies in rats found that long-term obesogenic diets increased hepatic oxidative stress and metabolic syndrome to a higher extent than short-term diets 46,47 . In a mouse model of breast cancer, caloric restriction was more efficient at reverting the carcinogenic effects of obesity than a low fat diet consumption 48 . Here consumption of a HFD for longer than one Other preclinical studies have found an immune cell-dependent effect of exercise in cancer 49 .…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Preclinical studies in rats found that long-term obesogenic diets increased hepatic oxidative stress and metabolic syndrome to a higher extent than short-term diets 46,47 . In a mouse model of breast cancer, caloric restriction was more efficient at reverting the carcinogenic effects of obesity than a low fat diet consumption 48 . Here consumption of a HFD for longer than one Other preclinical studies have found an immune cell-dependent effect of exercise in cancer 49 .…”
Section: Discussionmentioning
confidence: 96%
“…Preclinical studies in rats found that long-term obesogenic diets increased hepatic oxidative stress and metabolic syndrome to a higher extent than short-term diets 46, 47 . In a mouse model of breast cancer, caloric restriction was more efficient at reverting the carcinogenic effects of obesity than a low fat diet consumption 48 . Here consumption of a HFD for longer than one month diminished the anti-tumorigenic effects of PA in PDAC and speculate that the extended time on a HFD before the CD or PA interventions might generate more permanent epigenetic or metabolic changes that hinders the benefits of PA seen in our one-month intervention.…”
Section: Discussionmentioning
confidence: 96%
“…These data indicate that molecular subtype may be a stronger influencing factor than stage, but it is not the only factor influencing stromal gene expression. Biological factors such as genetics, age and breast density ( 45 47 ) and lifestyle factors such as diet ( 48 ) could potentially affect gene expression and contribute to heterogeneity of fibroblasts within groups. These same factors as well as technical factors in isolation and culture of fibroblasts and platforms used could have contributed to overall differences between our experimental dataset and published datasets.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence is also accumulating for several emerging mechanisms, including obesitydriven epigenetic reprogramming, immunosuppression, and gut dysbiosis. [43][44][45] In the context of these established and emerging mechanisms, four key questions have been raised. First, whereas it has become clear, primarily from bariatric surgery studies, that the pro-cancer effects of chronic obesity can be reversed by intentional weight loss.…”
Section: Established and Emerging Mechanisms Underlying The Obesity-c...mentioning
confidence: 99%
“…Data in rodent and human studies suggest that several cancer-related effects of obesity can persist even after moderate weight loss, and sustained weight loss may be required for significant cancer risk reduction in chronically obese mice or humans. 43,47,48 The impact of various forms of dietary restriction, including intermittent fasting and time-restricted feeding, on cancer risk or progression is an active area of research 49 and is likely to benefit from studies in canines, as discussed. Moreover, recent advances in pharmacologic approaches to induce robust and sustainable weight loss, such as tirzepatide, a novel glucagon-like peptide-1 and glucose-dependent insulinotrophic polypeptide receptor agonist, hold great promise, but these agents have not been well characterized in relation to obesity and cancer.…”
Section: Established and Emerging Mechanisms Underlying The Obesity-c...mentioning
confidence: 99%